The customer satisfaction toward supporting services of teaching and learning activities provided by USIM / Yusnida Mohd Pauzi - Mohd Pauzi, Yusnida (2009)
This research was conducted for the purposed of “The Customer Satisfaction toward Supporting Services of Teaching and Learning Activities Provided by USIM”. The main objective of this research was to identify the important of supporting services provided by Universiti Sains Islam Malaysia (USIM) to enhancing the level of student satisfaction of that service besides teaching and learning activities. The research is conducted using non-probability sampling method is convenience sampling. The questionnaire of this research was distributed to 150 respondents which 30 respondent each of the USIM’s Hostel. The Hostel are Sutera Indah,Jati, Nilam Court, Camelia Court and Pandan Mewah. The supporting services that influence student’s satisfaction such as attention, supporting and leading, learning environment and facilities, then to identify the USIM’s strategy and effective actions should be taken to enhance the their services. The conclusion of the research was the outcome from the data analysis and finding. Based on the finding, some recommendations have been suggested in order to help USIM’s Management and will enhance the student satisfaction.